(untitled) (Research, Society and Development, 2022)
The objective of this study was to compare the economic viability (EV) between traditional cropping systems (coivara) and agroforestry systems (AFS), with cumaru (Dipteryx spp.) as the main component in areas of family farmers (AF) of the PDS Terra Nossa (Novo Progresso-PA) and Kayapó indigenous people from the Baú Indigenous Land (TI) (Altamira-PA). To this end, participatory diagnoses and semi-structured interviews were carried out between 2015 and 2018. Data analysis was based on the time horizon of 4 years and 8 years. The EV was measured by the Net Present Value (NPV), Internal Rate of Return (IRR) and the benefit/cost ratio (B/C). The most frequent crops in the fields of AF of the Terra Nossa PDS (Novo Progresso) and the Kayapó indigenous peoples of the Baú Indigenous Land (TI) were banana and manioc. The economic analysis observed that the banana monoculture system (SMB) was the one that obtained the best results at 4 years, with a NPV of R 26,810.16, IRR of 32.62%, B/C of 2.56, with the planting of banana and cumaru (SAF2) with the second best result (NPV R 32,809.05, IRR of 29.39% and B/C of 3.18), and the cassava monoculture system (SMM) with the worse performance. On the other hand, when considering the time horizon of eight years, the SAF3 system showed better economic performance with a NPV of R 36,655.88, IRR of 25.76% and B/C of 3.15, and the second most profitable alternative was the AFS cumaru and banana (SAF2) (NPV R 32,809.05, IRR of 29.39% and B/C of 3.18).